Opportunity Exploitation in Times of the COVID-19 Pandemic – The Importance of Dynamic Capabilities and the Entrepreneur’s Characteristics - Kamila Malewska; Milena Ratajczak-Mrozek; Maja Sajdak (Problemy Zarządzania, 2021)
Purpose: The purpose of the paper is to answer the question of how entrepreneurs can take advantage of and exploit the conditions and opportunities resulting from the COVID-19 pandemic. Methodology: In the paper, we apply the conceptual review method in order to review extant knowledge, identifying important research gaps, and propose a conceptual framework for the research. Findings: We propose a conceptual framework of the recognition and exploitation of business opportunities during the COVID-19 pandemic. The framework assumes the influence of specific dynamic capabilities (strategic foresight – at the strategic level and innovation, self-structured and relational capabilities – at the operational level) and the entrepreneur’s key characteristics (being intuitive, having the ability to learn – especially in the field of crisis management, being innovative, having leadership competencies and having the ability to use advanced digital technologies) on the identification, creation and exploitation of opportunities during the COVID-19 pandemic. Research limitations: The main limitation results from the dynamism of the pandemic situation. Therefore, our results need further empirical verification. Practical implications: The model provides managerial implications for entrepreneurs responsible for decisions and actions during the pandemic crisis. We underline the importance of the development of entrepreneurs’ own competencies as well as the development of the competencies of their employees in the context of crisis management. We especially suggest that managers develop leadership competencies which relate to the competence of how to delegate powers and build empowerment in order to take advantage of the opportunities resulting from the effects of the COVID-19 pandemic. To exploit opportunities effectively, they should be recognized early, and therefore entrepreneurs should consider the benefits of using intuition in this area. Value: The special value of the paper can be seen in the context of the analysis. There is a shortage of studies identifying the impact of dynamic capabilities and the entrepreneur’s characteristics on the exploitation of opportunities during the specific situation of the COVID-19 pandemic.